2014
DOI: 10.1126/science.1247003
|View full text |Cite
|
Sign up to set email alerts
|

Neural Mechanisms of Object-Based Attention

Abstract: How we attend to objects and their features that cannot be separated by location is not understood. We presented two temporally and spatially overlapping streams of objects, faces versus houses, and used magnetoencephalography and functional magnetic resonance imaging to separate neuronal responses to attended and unattended objects. Attention to faces versus houses enhanced the sensory responses in the fusiform face area (FFA) and parahippocampal place area (PPA), respectively. The increases in sensory respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
406
4
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 472 publications
(445 citation statements)
references
References 74 publications
34
406
4
1
Order By: Relevance
“…In all of these studies, the representation of a task rule involved a unique stimulus-response mapping. Because PPC has been regarded as an interface between sensory and motor processing that facilitates sensorimotor transformations (Andersen and Cui, 2009), the representation of stimulusresponse mapping rules in PPC is expected. In the present study, the two tasks used involved identical motor responses, yet we still found robust representation of the task information.…”
Section: Discussionmentioning
confidence: 99%
“…In all of these studies, the representation of a task rule involved a unique stimulus-response mapping. Because PPC has been regarded as an interface between sensory and motor processing that facilitates sensorimotor transformations (Andersen and Cui, 2009), the representation of stimulusresponse mapping rules in PPC is expected. In the present study, the two tasks used involved identical motor responses, yet we still found robust representation of the task information.…”
Section: Discussionmentioning
confidence: 99%
“…Consider now an integrator that represents the item being presented; as information accumulates, the firing rate increases gradually---the moment of recognition occurs when a criterion rate is achieved (for a review, see (Shadlen and Kiani, 2013); see also section on consciousness). There has been progress in understanding the brain regions that control attention and the role of brain oscillations in the process (Baldauf and Desimone, 2014; Brooks et al, 2014; Buschman and Miller, 2009), but no clear mechanistic view of how the attentional window is selected has emerged.…”
Section: Visual Recognitionmentioning
confidence: 99%
“…PFC has traditionally been associated with executive control (for review, see (Miller and Cohen, 2001)), and working memory for locations and objects (Everling et al, 2006; Funahashi et al, 1989; Fuster and Alexander, 1971; Mendoza-Halliday et al, 2014; Miller et al, 1996; Rainer et al, 1998; Rao et al, 1997). Human imaging studies show that parts of PFC are active during both spatial and feature attention (Bressler et al, 2008; Egner et al, 2008; Gazzaley and Nobre, 2012; Giesbrecht et al, 2003), and a recent human MEG and fMRI study has reported that a particular region in PFC, the inferior frontal junction (IFJ), played an important role in the top-down control of feature-based attention (Baldauf and Desimone, 2014). …”
Section: Introductionmentioning
confidence: 99%